Course‐based undergraduate research experiences (CURES) as a pathway to diversify science. Issue 5 (15th August 2022) - Duboue, Erik R.; Kowalko, Johanna E.; Keene, Alex C.
Abstract: There is widespread recognition of the need to increase research opportunities in biomedical science for undergraduate students from underrepresented backgrounds. Here, we describe the implementation of team‐based science combined with intensive mentoring to conduct a large‐scale project examining the evolution of behavior. This system can be widely applied in other areas of STEM to promote research‐intensive opportunities in STEM fields and to promote diversity in science. Abstract : There is widespread recognition of the need to increase research opportunities in biomedical science for undergraduate students from underrepresented backgrounds. Here, we describe the implementation of team‐based science combined with intensive mentoring to conduct a large‐scale project examining the evolution of behavior. Highlight: Oliva et al. use course‐based undergraduate research experiences (CURE)‐based methodology for discovery‐oriented science. The structure of the CURE course is scalable with the potential to increase access to research.